Identification of gaps in students' knowledge of the Russian language - Israilova Gulnora Mamadzhanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals to bachelor students of pedagogical universities the educational, educational, developing tasks of the Russian language course, the content, goals and objectives of practical classes in the Russian language; aims to equip future teachers with the practice of learning in the teaching process; education in students of literacy. The purpose of the article is to fill the gaps in students' knowledge of the Russian language. Checking the filling of gaps in students. Performing certain training exercises, as well as considering directly in the classroom theoretical issues of practical importance.